Study of large strain behavior of OFHC copper: The role of polycrystal plasticity model. (July 2016) - Guo, X.Q.; Wu, P.D.; Wang, H.; Mao, X.B.; Neale, K.W.
Abstract: The large strain behavior of single-phase OFHC copper under different deformation processes are studied based on various polycrystal plasticity models including the classic Taylor-type model and various popular self-consistent models. The models are evaluated by comparing the predictions for the evolution of crystallographic texture and the stress–strain response in uniaxial compression and tension, plane strain compression, and simple shear against corresponding experiments. It is found that while the Taylor-type model is in reasonable first-order agreement with the experiments for the evolution of texture and the overall stress–strain response, the self-consistent models with grain interaction stiffness halfway between those of the limiting secant (stiff) and tangent (compliant) approximations give better results.